CONTRIBUTION AND PROJECTIONS OF THE PROCESSING INDUSTRY TO GRDP IN CENTRAL SULAWESI - Nur Rayhan Ardan Ramadhan; Rita Yunus; Santi Yunus (Jurnal Ilmu Ekonomi dan Pembangunan, 2025)
This research employed a quantitative descriptive approach to examine secondary data sourced from Central Sulawesi Province’s Central Statistics Agency (BPS). Specifically, the study delved into Gross Regional Domestic Product (GRDP) data from 2019 to 2023, aiming to analyze the manufacturing industry sector’s contribution and project its potential impact until 2028. Data analysis was conducted using the sector contribution formula and the least squares method. The findings revealed that the manufacturing industry sector consistently contributed an average of 29,76% to the province’s GRDP over the past five years. Projections based on the analysis suggest a promising 53% increase in the sector’s contribution to the GRDP in the subsequent five years.